Modelling of Human Transplacental Transport as Performed in Copenhagen, Denmark. (18th April 2014) - Mathiesen, Line; Mørck, Thit Aarøe; Zuri, Giuseppina; Andersen, Maria Helena; Pehrson, Caroline; Frederiksen, Marie; Mose, Tina; Rytting, Erik; Poulsen, Marie S.; Nielsen, Jeanette KS.; Knudsen, Lisbeth E.
Abstract Placenta perfusion models are very effective when studying the placental mechanisms in order to extrapolate to real‐life situations. The models are most often used to investigate the transport of substances between mother and foetus, including the potential metabolism of these. We have studied the relationships between maternal and foetal exposures to various compounds including pollutants such as polychlorinated biphenyls, polybrominated flame retardants, nanoparticles as well as recombinant human antibodies. The compounds have been studied in the human placenta perfusion model and to some extent in vitro with an established human monolayer trophoblast cell culture model. Results from our studies distinguish placental transport of substances by physicochemical properties, adsorption to placental tissue, binding to transport and receptor proteins and metabolism. We have collected data from different classes of chemicals and nanoparticles for comparisons across chemical structures as well as different test systems. Our test systems are based on human material to bypass the extrapolation from animal data. By combining data from our two test systems, we are able to rank and compare the transport of different classes of substances according to their transport ability. Ultimately, human data including measurements in cord blood contribute to the study of placental transport.